Residual Strength Estimation Method of Soft Coal Based on Equivalent Residual Strain Ratio - Qingquan Liu; Hao Ling; Yanfei Lu; Jia Lin; Yuanyuan Liu; Jing Wang; Wenyi Huang; Liang Wang (Geofluids)
In underground mining engineering, the residual strength of surrounding rock has an important influence on the secondary stress distribution caused by excavation. Generally, the residual strength of coal can be measured by experiments, but for soft coal, due to its large postpeak deformation characteristics and the limitation of strain sensor range, it is difficult to measure residual strength. Therefore, it is of great practical significance to estimate the residual strength of soft coal with incomplete stress-strain curves. In this paper, a method for estimating residual strength of soft coal based on the ratio of equivalent residual strain to peak strain is proposed. Taking advantage of the characteristics that the strain-softening curve of soft coal decreases approximately linearly in the initial stage, keeping the drop modulus unchanged, the endpoint of the extension line can be determined based on the ratio of equivalent residual strain to peak strain, which is estimated residual strength. There are 342 groups of typical complete stress-strain curves analyzed to determine the value range of the ratio of equivalent residual strain to peak strain. It is concluded that for briquette composed of soft coal, the ratio of equivalent residual strain to peak strain is between 1 and 3.35 when the confining pressure is 0-6 MPa, and the maximum probability interval of the ratio value under different confining pressures is further calculated. When the confining pressure is higher than 6 MPa, the briquette composed of soft coal tends to ideal plastic state after peak. The feasibility of the residual strength estimation method is verified by comparing the numerical simulation results of triaxial compression of coal pillars with the experimental results.